2022
DOI: 10.3390/antibiotics11060820
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Design and Implementation of the National Action Plan on Antimicrobial Resistance in the Philippines

Abstract: Antimicrobial resistance (AMR) is a global public health threat that warrants urgent attention. Countries developed their national action plans (NAPs) following the launch of the Global Action Plan on AMR in 2015. The development and implementation of NAPs are often complicated due to the multifaceted nature of AMR, and studies analyzing these aspects are lacking. We analyzed the development and implementation of the Philippine NAP on AMR with guidance from an AMR governance framework. We conducted in-depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Our study also reveals common factors for the occurrence of AMR including but not limited to selfmedication, under and overdose, wrong medication for the wrong disease, and treatment without diagnosis which ndings are similar to those reported from earlier studies [14][33] [34]. The results are also similar to a study in the eastern Haryana region which revealed cases of over-the-counter antibiotic sales (either without a prescription or by reusing old prescriptions) and farmers who were unaware of the harmful effects of certain types of antibiotics [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study also reveals common factors for the occurrence of AMR including but not limited to selfmedication, under and overdose, wrong medication for the wrong disease, and treatment without diagnosis which ndings are similar to those reported from earlier studies [14][33] [34]. The results are also similar to a study in the eastern Haryana region which revealed cases of over-the-counter antibiotic sales (either without a prescription or by reusing old prescriptions) and farmers who were unaware of the harmful effects of certain types of antibiotics [37].…”
Section: Discussionsupporting
confidence: 91%
“…In the bid to promote ecological civilization, several countries are adopting the use of antimicrobial agents in livestock production for the promotion of nutritional security [13]. This coupled with the transition to high-protein diets in the LMICs has caused animal production systems to be more intensive and antimicrobial drugdependent [14]. Small-scale farmers use human drugs to treat their animals due to several reasons which can be explored qualitatively to understand the underlying local context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 78 NAPs from around the world identified that the animal health and environment sectors were largely missing from many NAPs [ 34 ]. This resonates with the findings from other similar AMR studies conducted in Bangladesh, Malaysia, the Philippines, Tanzania, and Thailand [ 24 , 26 , 35 , 36 , 37 ]. In our previous study conducted in Singapore, we reported the need to address AMR in the animal health and environmental sectors as well [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although meetings were reportedly regular at the national level, meetings were reportedly seldom done at the lower levels. A local qualitative study on the implementation of another inter-agency program (antimicrobial resistance program) also reported a similar finding on the limited coordination across different levels of implementation and among relevant national agencies [ 17 ]. The former was linked to devolution which fragmented the health system into thousands of units that lacked coordination and varied greatly in resources for health [ 18 ].…”
Section: Discussionmentioning
confidence: 72%